A Critical Analysis of the Integration of Evidence-Based Practice among Nurses and Nursing Assistants and Its Impact on Patient-Centered Care in Multidisciplinary Healthcare Teams - Alobaid , Abdallah Ali H; Lasloom, Mesfer Mahdi A; Alsloom, Jaber Misfer A; Alkudhrah, Abdullah Dafer Z; Alsaloom , Hassan Musfer A; Alsaloom , Abdulrazaq Askar A; Al obeed, Ogab Ali Hamad; Almkayel , Mahdi Ali Hassan; al-yami , Mohammed Mesfer H; Lasloom , Hussien Mohammed A (Journal of Ecohumanism, 2024)
This article focuses on the implementation of EBP concerning nurses and nursing assistants and studies the effects of that implementation on the properly targeted and patient-specialized healthcare process with the help of MDTs. EBP is critical in today’s healthcare needs since it allows for the basis for decision-making and frames the latest practices influencing patients’ health. Nevertheless, there are challenges that nursing assistants face when implementing EBP in clinics because they have no formal training in EBPs. From the literature review and synthesis of this paper, we demonstrate the elements of EBP that improve team communication, patient satisfaction, and decreased medical errors, but what has been left unanswered is the experiences of the nursing assistants in EBP. Future strategies include evidence-based practice specialist schooling and hiring to catalyze increased EBP across multiple discipline teams and promote highly effective patient care.